Pengaruh Bahasa Belanda terhadap Perkembangan Bahasa Indonesia Analisis Historis dan Linguistik - Ghiyasah, Agis Muhammad; Moh. Fajar; Muhammad Nurrijki; Muhammad Zidan Fauziyana; Ahmad Fu'adin (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Language is a tool to support effective communication in conveying messages. Indonesian as a national language has experienced significant development in terms of vocabulary influenced by various foreign languages, one of which is Dutch. The main factor of the influence of Dutch in the development of Indonesian is the past history in which Indonesia was once colonized by the Dutch, the colonization caused language contact between two speakers of different languages in daily activities. This research method uses a qualitative research method with a literature review and the analysis technique applied is descriptive analysis. The interaction between the Dutch and Indonesian people during the colonial period occurred in various activities such as diplomacy, buying and selling, and spreading religion. In political history, it is recorded that Dutch has the same position as Malay, until Dutch was once used as the language of instruction in several schools in Indonesia at that time. In terms of linguistics, Dutch influences Indonesian in terms of lexical, grammatical, and changes in vowels and consonants. The influence of Dutch reflects the relationship between social status, scope of use and changes in language perception.